PENGEMBANGAN MODUL ELEKTRONIK BERBANTUAN ANDROID PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF - Utami, Prabawati Budi; Kuswanto, Heru (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2016)
This Research and Development (R & D) study develop an android-assisted electronic modules to study physics for eleventh grade students. Research subjects was students at one of senior highschools in Bantul. Critical and creative thinking skills average gain were 0.66 and 0.65 respectivto critical thinking skills and creative thinking skills respectively. There is a difference between the experimental class and control class with significance <0.05. This shows that the android-assisted electronic modules for learning the physics can be used to improve the critical and creative thinking skills students of class XI.